Cocaine/levamisole-induced systemic vasculitis with retiform purpura and pauci-immune glomerulonephritis - Veronese,F.V. (2016)
Levamisole has been increasingly used as an adulterant of cocaine in recent years, emerging as a public health challenge worldwide. Levamisole-associated toxicity manifests clinically as a systemic vasculitis, consisting of cutaneous, hematological, and renal lesions, among others. Purpura retiform, cutaneous necrosis, intravascular thrombosis, neutropenia, and less commonly crescentic nephritis have been described in association with anti-neutrophil cytoplasmic antibodies (ANCAs) and other autoantibodies. Here we report the case of a 49-year-old male who was a chronic cocaine user, and who presented spontaneous weight loss, arthralgia, and 3 weeks before admission purpuric skin lesions in the earlobes and in the anterior thighs. His laboratory tests on admission showed serum creatinine of 4.56 mg/dL, white blood count 3,800/μL, hemoglobin 7.3 g/dL, urinalysis with 51 white blood cells/μL and 960 red blood cells/μL, and urine protein-to-creatinine ratio 1.20. Serum ANCA testing was positive (>1:320), as well as serum anti-myeloperoxidase and anti-proteinase 3 antibodies. Urine toxicology screen was positive for cocaine and levamisole, with 62.8% of cocaine, 32.2% of levamisole, and 5% of an unidentified substance. Skin and renal biopsies were diagnostic for leukocytoclastic vasculitis and pauci-immune crescentic glomerulonephritis, respectively. The patient showed a good clinical response to cocaine abstinence, and use of corticosteroids and intravenous cyclophosphamide. Last serum creatinine was 1.97 mg/dL, white blood cell count 7,420/μL, and hemoglobin level 10.8 g/dL. In levamisole-induced systemic vasculitis, the early institution of cocaine abstinence, concomitant with the use of immunosuppressive drugs in severe cases, may prevent permanent end organ damage and associate with better clinical outcomes.